2021
DOI: 10.1007/s12646-021-00609-8
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Common Mental Disorders in Brazilian Parents During the COVID-19 Pandemic: Associated Factors

Abstract: COVID-19 pandemic has become a significant international public health problem. In addition to dealing with the pandemic's impact on mental health, parents need to cope with specific changes in their routines caused by social distance measures. This study aimed to investigate common mental disorders (CMD) symptoms in Brazilian parents during the COVID-19 pandemic and its associated factors. A total of 232 Brazilian parents ranging from 20 to 48 years old (M = 33.85; SD = 4.83) with children aged 1-36 months (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…In our study, parenting stress during lockdown was also associated with inattention symptoms in preschoolers one year later. Parents reported higher levels of stress during the pandemic ( Spinelli et al, 2020 ; Malhi et al, 2021 ; Riter et al, 2021 ). According to an Italian study, parent distress contributed to higher inattention/hyperactivity in children aged between 3 and 13 ( Marchetti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, parenting stress during lockdown was also associated with inattention symptoms in preschoolers one year later. Parents reported higher levels of stress during the pandemic ( Spinelli et al, 2020 ; Malhi et al, 2021 ; Riter et al, 2021 ). According to an Italian study, parent distress contributed to higher inattention/hyperactivity in children aged between 3 and 13 ( Marchetti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PS level was influenced by several factors, such as lower socioeconomic status, non-black-skinned people, living alone, receiving low social support, and offering high social support. A study carried out with Brazilian parents also identified that PS was the variable most strongly related to the CMD symptoms, showing that the higher the level of perceived stress, the greater the suspicion of these disorders [ 76 ]. Several factors have been associated with the occurrence of stress during the pandemic, which include concern about physical health and precautionary and disease control measures [ 76 ], anger and confusion arising from quarantine and social distancing [ 75 ], income reduction [ 75 , 76 , 77 ], fear of infection [ 75 ], and being part of a risk group for COVID-19 [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The American Psychological Association (APA) has stated that spending entire weeks at home (with limited resource supply, reduced stimulation, and curtailed social contacts) can seriously damage people's health and wellbeing, by intensifying the negative emotional states, such as fear, anxiety, depression, frustration, and/or irritability (APA, 2020). This has been demonstrated by a large number of studies examining the impact of COVID-19 (Cellini et al, 2020;Soraci et al, 2020;Riter et al, 2021;Singh and Quraishi, 2021;Zinchenko et al, 2021). Surbhi et al (2021) noted that Indian undergraduate students particularly experienced heightened fear, anxiety, and stress and attempted to address these negative feeling states by practicing gratitude.…”
Section: Technology and Emotional Well-beingmentioning
confidence: 99%